PERAN GURU DALAM MEMBENTUK KARAKTER SISWA DI SD NEGERI 2 SEPANG JAYA - Putra, Dwi Andika; Mashari, Ali; Wulandari, Oktri; Soraya, Rahayu (AHSANTA JURNAL PENDIDIKAN, 2024)
The problem in this research is the decline in students' morals from year to year, especially in terms of politeness and manners towards other people, which need to be emphasized consistently both at school and at home. This research aims to describe the role of teachers in character formation at SD Negeri 2 Sepang Jaya. The research method uses qualitative methods with a descriptive approach. The data collection techniques used were observation, interviews and documentation. Data were analyzed using Miles and Huberman data analysis. Data validity uses source triangulation and technical triangulation. The results of this research are, (1) The role of teachers in forming student character at SD Negeri 2 Sepang Jaya is carried out with several teacher roles, namely teacher as educator, teacher as demonstrator, teacher as class manager, teacher as motivator, and teacher as evaluator. (2) The supporting factors needed by teachers in forming student character at SD Negeri 2 Sepang Jaya are family environmental factors, infrastructure. (3) Meanwhile, the inhibiting factors for teachers in implementing student character formation at SD Negeri 2 Sepang Jaya are bad family environment factors and teacher factors.